2008
DOI: 10.1111/j.1365-3164.2008.00669.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study on canine atopic dermatitis and food‐induced allergic dermatitis in Switzerland

Abstract: Canine atopic dermatitis sensu stricto and food-induced allergic dermatitis are common canine skin conditions, which are often considered clinically undistinguishable. Several attempts have been made to describe populations of atopic dogs and determine breed predisposition but the results were often biased by the use of hospital populations as control group. The present study aims to describe a population of Swiss atopic and food-allergic dogs and to compare it with a data set representing more than 85% of all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
109
7
10

Year Published

2012
2012
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 112 publications
(138 citation statements)
references
References 27 publications
12
109
7
10
Order By: Relevance
“…In our study otitis externa was found in 49% of the dogs. Very similar findings were recently reported in surveys from five locations on three continents (Jaeger et al 2010) and also to other studies from Greece and Switzerland (Saridomichelakis et al 1999;Picco et al 2008).…”
Section: Lesions Of Dogs With Cadsupporting
confidence: 78%
See 4 more Smart Citations
“…In our study otitis externa was found in 49% of the dogs. Very similar findings were recently reported in surveys from five locations on three continents (Jaeger et al 2010) and also to other studies from Greece and Switzerland (Saridomichelakis et al 1999;Picco et al 2008).…”
Section: Lesions Of Dogs With Cadsupporting
confidence: 78%
“…Our data did not show any associations between breeds and the distribution of the other lesions of CAD, however, such associations have been reported (Picco et al 2008;Jaeger et al 2010;Wilhem et al 2011). The clinical significance of these findings is unclear, however, and none of these associations was included in the new criteria for the diagnosis of CAD (Favrot et al 2010).…”
Section: Lesions Of Dogs With Cadcontrasting
confidence: 38%
See 3 more Smart Citations